The Influence of Financial Literacy, Financial Behavior and Mental Accounting on the Consumptive Behavior of Mobile Legends Game Players - Putri, Edelweis Az-Zahra Fadlila Khaira Sufyan; Widyaningsih , Aristanti; S. Purnomo, Budi (Universitas Mohammad Husni Thamrin, 2025)
In recent years, the video game industry has grown rapidly, making it one of the largest entertainment sectors globally. In 2022, the total revenue of the gaming industry reached 185 billion USD, surpassing the music and film industries. This growth is driven by various business models, including game sales, subscriptions, in-game microtransactions, and digital advertising. Consumptive behavior in online games is increasing along with the ease of digital transactions. Previous studies related to financial literacy on consumptive behavior in the context of online games are still limited so that previous studies are difficult to find. Therefore, an understanding of the factors that influence players' financial decisions is needed, especially in the context of financial literacy, financial behavior, and mental accounting. This study aims to analyze the effect of financial literacy, financial behavior, and mental accounting on the consumptive behavior of Mobile Legends game players in Generation Z in Bandung City. This study uses a quantitative method with a descriptive and verification approach. Data were collected through questionnaires distributed to respondents using a purposive sampling method, namely Mobile Legends players from Generation Z in Bandung City. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS. The results of the study indicate that financial literacy has a negative effect on consumer behavior. Meanwhile, financial behavior and mental accounting do not have a negative effect on consumer behavior.